Radical islamic organizations against the surrounded enclavé-society - Arsyad Sobby Kesuma, Abdul Halim, (Opción, 2019)
The aim of the study is to investigate radical Islamic organizations against the surrounded Enclavé-Society via comparative qualitative research method. As a result, the radical Islamic organizations in Solo are complex entity among the steady and moderate people of Solo. In conclusion, radical Islamic organizations’ existence in Solo create a sociological category, that is, the surrounded society, a society that is surrounded by fear and worry, where bad values exist in human, groups, structural organizations, and ideology. The surrounded society is called a surrounded-enclave-society